Association of GBA genotype with motor and cognitive decline in Chinese Parkinson’s disease patients - Ren, Jingru; Zhou, Gaiyan; Wang, Yajie; Zhang, Ronggui; Guo, Zhiying; Zhou, Hao; Zheng, Huifen; Sun, Yu; Ma, Changyan; Lu, Ming; Liu, Weiguo (Frontiers in Aging Neuroscience, 2023)
Objective Variants in the glucocerebrosidase (GBA) gene are the most common and significant risk factor for Parkinson’s disease (PD). However, the impact of GBA variants on PD disease progression in the Chinese population remains unclear. This study aimed to explore the significance of GBA status on motor and cognitive impairment in a longitudinal cohort of Chinese patients with PD. Methods The entire GBA gene was screened by long-range polymerase chain reaction (LR-PCR) and next generation sequencing (NGS). A total of 43 GBA-related PD (GBA-PD) and 246 non-GBA-mutated PD (NM-PD) patients with complete clinical data at baseline and at least one follow-up were recruited for this study. The associations of GBA genotype with rate of motor and cognitive decline, as measured by Unified PD Rating Scale (UPDRS) motor and Montreal Cognitive Assessment (MoCA), were assessed by linear mixed-effect models. Results The estimated (standard error, SE) UPDRS motor [2.25 (0.38) points/year] and MoCA [−0.53 (0.11) points/year] progression rates in the GBA-PD group were significantly faster than those in the NM-PD group [1.35 (0.19); −0.29 (0.04) points/year; respectively]. In addition, the GBA-PD group showed significantly faster estimated (SE) bradykinesia [1.04 (0.18) points/year], axial impairment [0.38 (0.07) points/year], and visuospatial/executive [−0.15 (0.03) points/year] progression rates than the NM-PD group [0.62 (0.10); 0.17 (0.04); −0.07 (0.01) points/year; respectively]. Conclusion GBA-PD is associated with faster motor and cognitive decline, specifically greater disability in terms of bradykinesia, axial impairment, and visuospatial/executive function. Better understanding of GBA-PD progression may help predict prognosis and improve clinical trial design.